Genetika Bani Adam dalam Perspektif Tafsir Ilmi: Telaah Pemikiran Thanthawi Jauhari dalam al-Jawahir - Rojikin, Heru; Hasbi, Artani; Huda, Ade Naelul (Adh Dhiya | Journal of The Quran and Tafseer Studies, 2025)
The number of people in the world is counted in billions. When looked back upon, it surely goes back to Prophet Adam (peace be upon him) and Mother Eve. When they both met, their descendants emerged. The children of Adam originated from their father, Adam (peace be upon him), who was created from microbes. Each of them spread, carrying atoms, and to this day they have not disappeared. From this, the question arises: what is Thanthawi Jauhari's thinking about the genetics of the descendants of Adam (peace be upon him)? This research will be qualitatively analyzed using a scientific approach. The primary data source used in this research is the book al-Jawahir fi Tafsir al-Qur’an al-Karim by Thanthawi Jauhari, which will be analyzed descriptively and analytically. This research concludes that human beings on Earth, from the past to the present, have one common point, which is the unity in creation and similarity in characteristics, conditions, and behavior. This unity and similarity are caused by each human passing down genes to the next generation, which will continue to process and intermix according to human reproduction and dissemination itself. This means every child carries genes from their parents all the way back to Prophet Adam (peace be upon him). The genetic processes known in Mendel's theory can harmonize with the clear signals from the Qur’an as articulated in Jauhari's interpretation.